Budżetowanie kapitałowe w strategicznym controllingu działalności marketingowej - Nowak, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article treats of application of capital budgeting in strategic marketing controlling. It is based on the assumption that investment in relationship with a client is a specific form of investment. Therefore they ought to be measurable b usage of the same techniques and methods which are applied to the other investment forms. As both academics and financial managers agree that discounted methods, especially NPV technique are most objective, this technique should be used while evaluating client relation investments. In this context CLV (Customer Lifetime Value) should be used. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 296-301